II. The History of our Foreign Trade Balance During the Great War - Bullock, Charles J.; Williams, John H.; Tucker, Rufus S. (The Review of Economics and Statistics, 1919)
Charles J. Bullock, John H. Williams, Rufus S. Tucker, II. The History of our Foreign Trade Balance During the Great War, The Review of Economics and Statistics, Vol. 1, No. 3 (Jul., 1919), pp. 234-252